Analisis Visual Perubahan Tipografi pada Logotype Telkomsel - Yassinta Fitria; Rafif Virgian Darmanto (Jurnal Ilmiah Wahana Pendidikan, 2023)
The development of letters will always be felt from time to time as if they continue to live with the times. Humans need letters as intermediaries for interaction with their surroundings, making letters a form of communication. The context of letters is studied in the science of typography. Broadly speaking, typography is defined as the study of the shape and character of letters. The influence of typography is very large in this global era, especially in the field of marketing. What is the process of structuring typography in the media used to attract consumers? Likewise, Telkomsel has just changed its logo in 2021. The fonts and typographical elements in the Telkomsel logo have undergone drastic changes in terms of visual appearance. The analysis of changes to the Telkomsel logo involves the basic elements of typography, namely readability, legibility, visibility, as well as clarity, namely the level of one's legibility in understanding the shape of the letters.